Comparison efficacy and safety sodium valproate versus combination sodium valproate and levetiracetam for treatment epilepsy in children: a meta-analysis - Gasti, Detria Rahma; Hapsari, Aulia Sita; Ulifah, Karima Iffani (Medical Faculty of Brawijaya University, Indonesia, 2023)
Background: The most prevalent severe neurological condition, impacting more than 50 million individuals globally, is epilepsy. A new anti-epileptic drug (AED) called levetiracetam (LEV) has shown promise as an adjuvant treatment for children's treatment-resistant partial-onset seizures. Sodium valproate (SV) is a commonly used anti-epileptic medication that has a range of effects and a distinct mode of action. Combining LEV and SV has emerged as a viable clinical treatment plan. This study aimed to use meta-analysis to estimate the safety and effectiveness of LEV with SV in pediatric epilepsy patients. Methods: From January 1993 to April 2023, the Cochrane Library, PubMed, and ScienceDirect were searched. The included literature consisted of randomized controlled clinical trials that examined the use of SV in conjunction with LEV in pediatric epileptic patients. This meta-analysis followed the PRISMA guidelines. The statistical program used for the meta-analysis was Revman V.5.4.1. Results: From 568 original titles screened, data were extracted from 3 studies (n=303). Compared with SV alone, SV combined with LEV significantly improved the overall therapeutic effect of epilepsy (OR=0.80; 95%CI= 0.72-0.89; p<0.0001). The observation group significantly reduced the occurrence of adverse drug reactions (ADRs) of nausea and vomiting (OR=2.77; 95%CI=1.08-7.09; p=0.03). Conclusion: According to this meta-analysis, SV plus LEV considerably increased the overall therapeutic effect of epilepsy while concurrently lowering the incidence of ADRs when compared to SV alone. Thus, for treating epilepsy in children, we advise SV in conjunction with LEV.